Answer:
The value of the given expression is
[tex]\frac{sin4A-2sin2A}{sin4A+2sin2A}=-a^2[/tex]
Step-by-step explanation:
Given that [tex]tanA=a[/tex]
To find the value of [tex]\frac{sin4A-2sin2A}{sin4A+2sin2A}=-a^2[/tex]
Let us find the value of the expression [tex]\frac{sin4A-2sin2A}{sin4A+2sin2A}=-a^2[/tex]:
[tex]\frac{sin4A-2sin2A}{sin4A+2sin2A}=\frac{2cos2Asin2A-2sin2A}{2cos2Asin2A+2sin2A}[/tex] ( by using the formula [tex]sin2A=2cosAsin2A[/tex] here A=2A)
[tex]=\frac{2sin2A(cos2A-1)}{2sin2A(cos2A+1)}[/tex]
[tex]=\frac{(cos2A-1)}{(cos2A+1)}[/tex]
[tex]=\frac{-(sin^2A+cos^2A-cos2A)}{sin^2A+cos^2A+cos2A}[/tex] (using [tex]sin^2A+cos^2A=1[/tex] here A=2A)
[tex]=\frac{-(sin^2A+cos^2A-(cos^2A-sin^2A))}{sin^2A+cos^2A+(cos^2A-sin^2A)}[/tex](using [tex]cos2A=cos^2A-sin^2A[/tex] here A=2A)
[tex]=\frac{-(sin^2A+cos^2A-cos^2A+sin^2A)}{sin^2A+cos^2A+(cos^2A-sin^2A)}[/tex]
[tex]=\frac{-(sin^2A+sin^2A)}{cos^2A+cos^2A}[/tex]
[tex]=\frac{-2sin^2A}{2cos^2A}[/tex]
[tex]=-\frac{sin^2A}{cos^2A}[/tex]
[tex]=-tan^2A[/tex] ( using here A=2A )
(since tanA=a given )
Therefore [tex]\frac{sin4A-2sin2A}{sin4A+2sin2A}=-a^2[/tex]